The utility of passive acoustic monitoring for using birds as indicators of sustainable agricultural management practices - Molina-Mora, Ingrid; Ruíz-Gutierrez, Viviana; Vega-Hidalgo, Álvaro; Sandoval, Luis (Frontiers in Bird Science, 2024)
Agriculture, which is spreading rapidly, is one of the major effectors on biodiversitygenerally contributing to its decline. In the past few decades, most research efforts have focused on examining the impact of different agricultural practices on biodiversity. However, less attention has been paid on examining the impact of different agricultural management practices on biodiversity. Some of the main challenges are driven by the inconvenient nature of some of the practices (e.g. pesticide application), as well as the season and timing chosen for them (e.g. tree pruning). Here, we provide the utility of using passive acoustic monitoring techniques to examine the impact of agricultural management practices, using birds as indicators of biodiversity. We describe what factors should be considered in terms of the ecology and behavior of the bird community, factors that affect the ARU sampling regime, and how to store and analyze the data. To illustrate our recommended approach, we present a case study focused on looking at the effect of two prevalent management practices in coffee: pruning and pesticide application. We examined these effects in a coffee landscape in Costa Rica over two years, by restricting our analyses to a few focal species, and by using a subsample of the total hours recorded in combination with a mobile application platform developed to facilitate the annotations of recordings. Our results showed most species were negatively affected by pruning, while all species were negatively affected by pesticide application. In conclusion, our approach for leveraging technology to examine the impacts of agricultural management practices should allow for research that can be beneficial to guide and evaluate investments in regenerative agricultural practices that are aimed to balance biodiversity conservation with human well-being.